(untitled) (Minerva, 2017)
On the basis of a large corpus of data, the paper anaylses suffixes -τρον, τρᾱ, -θρον and -θρᾱ. The data reveal that in Ancient Greek -θρον and -θρᾱ are allomorphs of -τρον and -τρᾱ, respectively. The functioning and distribution governing these allomorphs can explain other similar phenomena in Ancient Greek.